Whole‐exome sequencing in an individual with severe global developmental delay and intractable epilepsy identifies a novel, de novo GRIN2A mutation. Issue 7 (5th June 2014) - Venkateswaran, Sunita; Myers, Ken A.; Smith, Amanda C.; Beaulieu, Chandree L.; Schwartzentruber, Jeremy A.; FORGE Canada Consortium; Majewski, Jacek; Bulman, Dennis; Boycott, Kym M.; Dyment, David A.
Summary We present a 4‐year‐old girl with profound global developmental delay and refractory epilepsy characterized by multiple seizure types (partial complex with secondary generalization, tonic, myoclonic, and atypical absence). Her seizure semiology did not fit within a specific epileptic syndrome. Despite a broad metabolic and genetic workup, a diagnosis was not forthcoming. Whole‐exome sequencing with a trio analysis (affected child compared to unaffected parents) was performed and identified a novel de novo missense mutation in GRIN2A, c.2449A>G, p.Met817Val, as the likely cause of the refractory epilepsy and global developmental delay. GRIN2A encodes a subunit of N‐methyl‐d‐aspartate (NMDA) receptor that mediates excitatory transmission in the central nervous system. A significant reduction in the frequency and the duration of her seizures was observed after the addition of topiramate over a 10‐month period. Further prospective studies in additional patients with mutations in GRIN2A will be required to optimize seizure management for this rare disorder. This report expands the current phenotype associated with GRIN2A mutations. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.